2008
DOI: 10.1063/1.2932166
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy-type defects in Er-doped GaN studied by a monoenergetic positron beam

Abstract: A relationship between intra-4f transitions of Er and vacancy-type defects in Er-doped GaN was studied by using a monoenergetic positron beam. Doppler broadening spectra of the annihilation radiation were measured for Er-doped GaN grown by molecular beam epitaxy. A clear correlation between the defect concentration and the photoluminescence ͑PL͒ intensity was observed. The major defect species detected by positrons was identified as a Ga vacancy V Ga , and its concentration increased with increasing Er concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
5
18
0
Order By: Relevance
“…Er-doped GaN samples were grown on sapphire substrates by gas-source molecular beam epitaxy [16,17]. Metallic Ga and Er were evaporated from conventional Knudsen effusion cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Er-doped GaN samples were grown on sapphire substrates by gas-source molecular beam epitaxy [16,17]. Metallic Ga and Er were evaporated from conventional Knudsen effusion cells.…”
Section: Methodsmentioning
confidence: 99%
“…Fig. 4 shows the relationship between the S values in Er-doped GaN and the Er concentration [Er] [17]. The variation of the integrated intensity of the 511 nm PL line is also shown.…”
Section: Vacancy-type Defects In Ion-implanted Ganmentioning
confidence: 98%
“…As an ion, Eu can exist in two oxidation states: Eu 2 þ and Eu 3 þ , with the former being rarely encountered in semiconductors. Several studies have been done on Eu in GaN both theoretically [2][3][4]9,10] and experimentally [11][12][13][14][15][16][17][18]. However, to the best of our knowledge, it is only Auret et al [16] who recently experimentally observed a metastable defect with charge-state controlled metastability in 300 keV Eu doped GaN, annealed at 1000 1C.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, doping procedures of magnetic impurities have been reported to introduce cation vacancies and their complexes. 15) At this stage, it is imperative to examine yet-to-be-discovered intrinsic spin-related properties of defects in nitride semiconductors.…”
mentioning
confidence: 99%